Voluntary Surveillance Program for Equine Influenza Virus in the United States from 2010 to 2013. (14th January 2015) - Pusterla, N.; Kass, P.H.; Mapes, S.; Wademan, C.; Akana, N.; Barnett, C.; MacKenzie, C.; Vaala, W.
<x xml:space="preserve">Abstract</x> Background Recent surveillance studies for equine respiratory viruses have shown that equine influenza virus (EIV) continues to be a prevalent respiratory virus of equids throughout the United States and Europe. Objectives To gain a better understanding of the prevalence and epidemiology of EIV shed by horses, mules and donkeys in the United States from March 2010 to November 2013. Animals 2, 605 equids. Methods Nasal secretions from index cases with acute onset of respiratory disease were tested by qPCR for EIV. Multilevel logistic regression was used to model the association between EIV status and prevalence factors. Furthermore, observations from EIV‐positive study horses were compared to previous data from March 2008 to February 2010. Results A total of 230 (9.7%) index cases tested qPCR positive for EIV. A higher‐than‐expected proportion of EIV qPCR‐positive horses occurred in the 1–5, 6–10, and 11–15 age groups when compared to the <1 year of age group. Fever, nasal discharge and coughing were positively associated with EIV‐positive horses. EIV qPCR‐positive study cases were significantly older and more often vaccinated against EIV compared to EIV qPCR‐positive animals from the 2008‐2010 study period. Conclusions and Clinical Importance This study provides valuable and contemporary information on the frequency of EIV detected by qPCR in the United States. The results also underscore that older and previously vaccinated horses were susceptible to EIV.